International Regulation and Bank Performance: A Bibliometric Analysis - Elidrissi, Hajar Bassim; El Bouazizi, Said (International Journal of Economics and Financial Issues, 2026)
Banking regulation has progressively evolved as a central mechanism for enhancing bank performance, financial stability, and systemic resilience. In the aftermath of the global financial crisis, regulatory frameworks have shifted from predominantly microprudential approaches toward more integrated macroprudential perspectives. Nevertheless, despite the expansion of the literature, its intellectual structure and global influence remain insufficiently synthesized. Against this backdrop, this study aims to systematically map the scientific production on international banking regulation and banking performance. To this end, a large-scale bibliometric analysis was conducted using data from Web of Science, Scopus, ScienceDirect, SSRN, and EconLit, covering the period up to January 2026. After deduplication, 9,095 publications were examined using bibliometrix, SciVal, and VOSviewer, with a focus on thematic structures, collaboration networks, and normalized citation impact. The findings indicate a marked increase in publications, particularly after 2015, in line with Basel III implementation and post-pandemic regulatory challenges. Moreover, the literature is primarily structured around financial stability, systemic risk, and risk management. Citation indicators further reveal a strong global impact, with a significant share of highly cited publications and an average FWCI above the world benchmark. Overall, the results point to a growing shift toward a resilience-oriented regulatory paradigm, offering relevant insights for both researchers and policymakers.